Possession and Dispossession Performing Jewish Ethnography in Jerusalem - Mauas, Lea; MacQueen, Michelle; Rotman, Diego (De Gruyter, 2022)
When different types of knowledge and practice meet, they enrich each other. This book reflects on this meeting of divergent processes in Jerusalem. The contributions attempt to challenge the apparent division between contemporary art and ethnography, between tradition, preservation and representation, in an approach the editors call "contemporary ethnography," where the borders between ethnography and contemporary art are blurred.